German studies in Africa: towards “Pan-African Germanistik” (2018)
This paper explores the conflict of interests between Pan-Africanist aspiration for an Africa (and her Diaspora) that is self-confident and free from cultural and other forms of foreign domination and the discipline of Germanistik1 in postcolonial Africa that represents German nationalist aspirations and advances in Euro-Western cultural identity ideals. This conflict resonates the paradox of being a Germanist and a Pan-Africanist that is relevant to the study, learning and teaching of 'things German'2 in institutions of learning in Africa. Adopting historical comparative and critical intercultural analyses of secondary historical and ideational data sourced through close reading, the paper reviews the respective (pan-nationalist) conceptualization and history of Pan-Africanism and Germanistik, examines the cultural context of conflict between the two and the mediatory approaches to the conflict in the study and teaching of 'things German' in Africa. The paper concludes that Germanistik needs to be 'truly' reinvented as “African-Germanistik” in the African postcolonial educational environment for it to reconcile itself with the aspirations of Africans and build a synthesis for mutual acceptance, cooperation, and development.